(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article is devoted to the study of issues of improving and implementing the electronic tax system in Uzbekistan, as well as the development and improvement of electronic services for tax authorities and taxpayers. The article provides information about tax services, assessing their reliability, as well as online services for monitoring cash register equipment. In addition, further prospects for electronic tax services and the implementation of smart tax services were considered.